A Qualitative Study on the Dynamics of Direct Feedback from Supervisors on Employee Performance Improvement at PT Wangsa Jatra Lestari - Najwa Shafira Devina; Muafi Muafi (Danadyaksa: Post Modern Economy Journal, 2026)
This research entitled A Qualitative Study on the Dynamics of Direct Feedback from Supervisors on Employee Performance. Improvement at PT Wangsa Jatra Lestari is a study that discusses the Role of direct feedback from supervisors in supporting employee performance. improvement. It aims to observe: (1) the forms and processes of direct feedback provided by supervisors to employees; (2) the factors influencing the effectiveness of feedback in improving performance.; and (3) employees’ perceptions toward the feedback received. This qualitative research used a case study approach and the data were collected through in-depth interviews and documentation. The informants consisted of management and employees who were directly involved in the feedback process. The data validity was tested using credibility and source triangulation. The data analysis technique was conducted through data reduction, data presentation, and drawing conclusions systematically. The results of this research showed that direct feedback from supervisors plays an important Role in improving employee performance., in terms of work quality, timeliness, accuracy, and work motivation. The forms of feedback consist of positive, corrective, and Developmental feedback delivered directly through face-to-face communication and daily work activities. The effectiveness of feedback is influenced by the clarity of delivery, timing of feedback, interpersonal relationships between supervisors and employees, and the communication skills of supervisors in conveying messages appropriately. Employees’ perceptions toward feedback tend to be positive as it helps them understand mistakes, improve work methods, increase self-confidence, and strengthen working relationships with supervisors. The findings also indicate several obstacles, including the absence of written standard operating procedures (SOP) regarding feedback, differences in employee characteristics and understanding, as well as variations in supervisors’ communication abilities in delivering feedback.